From Empty Shops to Vibrant Communities: Adaptive Reuse as a Sustainable Response to Retail Decline - Münster, Mia B.; Adriansen, Hanne Kirstine (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
Rapid and significant reductions in global carbon emissions are needed to remain within Earth’s limits. The construction and operation of buildings account for the largest share of the global consumption of raw materials, and they yield around 40% of global carbon emissions. Leading climate researchers therefore recommend adapting housing needs to existing building stock instead of constructing new buildings. This requires shifting the focus from what we desire to how we can adapt our needs to existing spaces. This paper, a work in progress, examines the misalignment between sustainability ambitions and tourism strategy in a Danish municipality. This municipality has yet to fully integrate the potential of its existing building stock into its tourism plans. This oversight is striking, given the municipality’s ambitious goal of achieving CO₂ neutrality and availability of surplus building stock, including vacant retail spaces in shopping streets. Building on this observation, we propose a conceptual framework for incorporating existing buildings into the municipality’s tourism strategies. Rather than expanding their climate footprint by constructing new accommodations for tourists, we suggest a solution centered on using vacant spaces and renovating existing structures. Specifically, we envision repurposing vacant retail spaces into holiday apartments, boutique hotels, or other types of housing. This paper lays a foundation for further research to increase awareness of this issue and to test and refine our proposal. The overarching goals are to support sustainable urban development, promote climate-friendly behavior, and strengthen local community and economic vitality in small and medium-sized towns through longer-lasting buildings.